Untapped Possibilities of Antiischemic Therapy after Acute Myocardial Infarction: Data from the PROFILE-IM Register - E. P. Kalaydzhyan; S. Yu. Martsevich; N. P. Kutishenko; D. P. Sichinava; O. M. Drapkina (Столичная издательская компания, 2020)
Aim. To evaluate the practice of prescribing antianginal/antiischemic therapy in patients who, after acute myocardial infarction (AMI), retained typical clinical manifestations of stable angina.Material and methods. The registry includes 160 patients who applied to the polyclinic from March 01, 2014 to June 30, 2015 after suffering an AMI. Anti-ischemic therapy was evaluated in patients with typical angina pectoris.Results. Based on the survey, typical angina attacks were detected in almost a quarter of patients (38 patients - 23.8%). According to the main indicators, patients with typical angina pectoris practically did not differ from the rest of the group of patients, with the exception of a significantly larger proportion of patients with diagnosed ischemic heart disease before AMI and patients under dispensary supervision. Almost all patients received beta-blockers (97.4%), about a third of patients received calcium antagonists (28.9%) or long-acting nitrates (34,2%). During the first year after AMI, second-line drugs were practically not prescribed to enhance antianginal therapy. According to international non-proprietary names, the choice of doctors tended to prescribe bisoprolol, amlodipine, and isosorbide dinitrate. Exacerbation of the disease course with hospitalization for unstable angina pectoris was recorded in 9 (23.7%) patients from the group with typical angina pectoris and in 5 (4.1%) patients in the rest of the group (p<0.001).Conclusion. In real clinical practice, only a small part of patients with typical angina pectoris receive drug therapy that corresponds to evidence-based medicine; therefore, the unique possibilities of antianginal (anti-ischemic) therapy often remain unrealized.